2007
DOI: 10.1159/000097700
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of Seven Neuron-Specific Enolase Assays

Abstract: We have previously shown that interferon-gamma (IFN-gamma) inhibits expression of the metastasis-promoting protein S100A4. In the present study, we further explore the mechanism behind the IFN-gamma-mediated effects on the human S100A4 promoter and demonstrate that IFN-gamma represses S100A4 promoter activity through induction of the class II transactivator (CIITA). The acidic domain in the N-terminal part of CIITA was crucial for the observed IFN-gamma-induced inhibition of S100A4 promoter activity, probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Although a systematic review suggested that an NSE serum level of >33μg/liter is a reliable predictor in patients after CPR, data on several patients with good outcomes despite much higher NSE levels have since been reported 4, 25. This can probably be explained by different laboratory methods used to determine NSE levels and other clinical factors such as hemolysis, which can lead to high NSE levels unrelated to brain damage 26, 27. Data on NSE levels after hypothermia are again conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Although a systematic review suggested that an NSE serum level of >33μg/liter is a reliable predictor in patients after CPR, data on several patients with good outcomes despite much higher NSE levels have since been reported 4, 25. This can probably be explained by different laboratory methods used to determine NSE levels and other clinical factors such as hemolysis, which can lead to high NSE levels unrelated to brain damage 26, 27. Data on NSE levels after hypothermia are again conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal time point differs among the predictors. Also, the predictive value varies in different studies and cut‐off values are dependent of the assay used …”
Section: Discussionmentioning
confidence: 99%
“…The search for a reliable biomarker to improve prognostication has proven difficult . Most interest has been focused on brain‐derived biomarkers, where neuron‐specific enolase (NSE) is the best studied and was recommended by practice guidelines prior to the era of temperature management …”
mentioning
confidence: 99%